“My Jijii would always tell me: We're getting you ready. We're getting you ready”: Indigenous presencing in adventure tourism - Koe, Bobbi Rose; Loukes, Keira A. (Frontiers in Sustainable Tourism, 2024)
While there has been a general increase in Indigenous-owned and operated tourism companies across Turtle Island (currently known as North America), the same is not true for what is commonly referred to as “adventure tourism”, and specifically, in whitewater river canoe and raft guiding. There are still several barriers that continue to keep many prospective Indigenous guides out of the industry and off their traditional lands. This can work to perpetuate the myth that adventure tourism marketing relies on, that the rivers, lakes, and land they guide their clients on are an untouched and unpeopled “wilderness”. Peel River Watershed protector and activist Bobbi Rose Koe started an adventure tourism company, Dinjii Zhuh Adventures, to address these inequities. She aims to change the culture of guiding and tourism through introducing more Indigenous youth to their traditional watersheds, to train them as whitewater canoeing and rafting guides, and to support them in their employment and career development with the ultimate goal of land protection. This paper, co-written as a dialogue guided by the voice and perspective of Bobbi Rose, will weave together a story of the impact Indigenous presence has on the land, Indigenous youth, non-Indigenous guides and clients, other tourist operators, and the industry in general. Our conversation begins and ends with the role Indigenous presence plays in land and cultural governance and protection. We share these conversations, opportunities, challenges, and imagined futures to invite tourism researchers, operators, and guides to reflect, as well as to offer encouragement and camaraderie to other Indigenous guides and tourist operators.